How does the water flow? And does data follow it? - Henrik Dissing (Geoforum Perspektiv)
Climate adaptation and effective flood management require accurate and accessible data on water levels and water flow. In consultation with the Danish Geological Survey (GEUS), the Danish municipalities association (KL), and the Danish Environmental Protection Agency as well as the private companies WatsonC, DRYP, and WSP, Denmark's Environmental Portal (DMP) has developed an IT system for water levels, water flow and groundwater level measurements. The system makes it possible to compile data from different loggers in near real time.